Experimental study on the drag reduction performance of sodium alginate in saline solutions - Zhensong Cheng; Xin Zhang; Xiaodong Dai; Hengli Zhai; Xinwang Song; Xudong Wang; Liang Gao; Guoxin Zhang; Yuan Lu; Lei Li; Xiu Yan; Jianhua Zhang (Scientific Reports)
Abstract Since the discovery of the turbulence drag reduction phenomenon over 70 years ago, it has been recognized that the addition of small quantities of drag-reducing agents to fluids can significantly decrease wall shear stress, thereby enhancing fluid pumpability. In many applications, the fluids often contain salts, such as those used in fracturing processes within the petroleum sector. The aim of this study is to experimentally investigate the effects of salinity, flow rate, and polymer concentration on the drag reduction performance of sodium alginate in circular pipes. The experimental process was designed using Response Surface Methodology (RSM), and a predictive regression model for the drag reduction rate (DR) was developed. By comparing the predicted results with the experimental outcomes, we found that the accuracy of the predictive model is high, with the error controlled within ± 20%. To provide a more intuitive understanding of the effect of salinity on the drag reduction performance of sodium alginate, this paper introduces the innovative concept of Drag Reduction Inhibition Rate (ε). The results indicate that the drag reduction rate in saline solutions is generally lower than that in salt-free solutions. However, during the initial stage of turbulence, a small amount of salt facilitates the unfolding of sodium alginate molecules, thereby enhancing the drag reduction effect (ε > 100%). Following this initial turbulent phase, the inhibitory effect of salinity on the polymer becomes pronounced, causing the drag reduction inhibition rate to decrease from 115 to 20%. We propose that high concentrations of salt may restrict the extent of polymer unfolding, resulting in concentrated solutions degrading into dilute solutions.